Personalized Ahara and Vihara: Aligning Diet and Lifestyle with Prakriti in Ayurveda for Optimal Health. - Thakur, Ritu; Jagota, Ankush; Thakur, Shalini (International Research Journal of Ayurveda & Yoga, 2024)
Background: In Ayurveda, Diet (Ahara) and Lifestyle (Vihara) play a crucial role in maintaining overall health and wellbeing, and it is tailored to an individual’s unique constitution or “Prakriti,” which is determined by the unique balance of the three doshas: Vata, Pitta, and Kapha. Each dosha represents distinct physical and psychological characteristics that influence health and wellness. Material and Methods: The diet and lifestyle according to various Samhitas such as Charak and Sushruta Samhita were studied, and a plan was made according to Prakriti. Result: This study suggests that aligning diet and lifestyle with one’s prakriti may help in preventing lifestyle-related diseases but also enhance mental clarity, emotional stability, and energy levels. Discussion & Conclusion A balanced diet and lifestyle tailored to one’s dosha and prakriti enhance digestion and vitality, and a moderated lifestyle fosters overall well being. By integrating these principles, individuals can achieve holistic health tailored to their unique constitution or prakriti.